Early clinical outcomes of bipolar hemiarthroplasty for femoral neck fractures in elderly patients using the OCM approach: a retrospective study - Zheng, Hongming; Kong, Danhui; He, Shuangjun; Jiang, Boyi; Zhu, Dongbo; Wu, Shuhua; Wang, Yaowei; Zhou, Lijian; Xia, Yan (Frontiers in Surgery, 2024)
Objective This study aims to assess the early clinical outcomes of bipolar hemiarthroplasty for treating femoral neck fractures in elderly patients aged 75 and above using the Orthopädische Chirurgie München (OCM) approach. Methods A retrospective analysis was conducted on a cohort of 95 elderly patients who underwent bipolar hemiarthroplasty for Garden Type III and IV femoral neck fractures between January 2020 and December 2022. The participants were categorized into two groups according to the surgical approach used: the OCM approach and the posterior-lateral approach (PLA). The average follow-up duration was 11.20 ± 2.80 months for the OCM group and 11.12 ± 2.95 months for the PLA group, with both groups ranging from 6 to 18 months. Clinical outcomes assessed included surgical duration, incision length, postoperative hospital stay, time to ambulation, hemoglobin levels, serum creatine kinase (CK) levels, C-reactive protein (CRP) levels, pain (assessed using the Visual Analogue Scale, VAS), and functional recovery (evaluated through Harris hip scores). Additionally, complications such as intraoperative and postoperative fractures, deep vein thrombosis, wound infection, nerve injury, postoperative dislocation, leg length discrepancy, and Trendelenburg gait were monitored. Results There was no significant difference in the surgical duration between the OCM and PLA groups. However, the OCM group exhibited shorter incision lengths, reduced postoperative hospital stays, and earlier ambulation times compared to the PLA group. Significantly lower intraoperative blood loss, smaller decreases in hemoglobin levels on postoperative days 1 and 3, lesser hidden blood loss, and decreased levels of CK and CRP were observed in the OCM group. Pain levels, measured by VAS scores, were lower, and Harris hip scores, indicating functional recovery, were higher at 2 and 6 weeks postoperatively in the OCM group than in the PLA group. The incidence of complications, such as periprosthetic fractures, intramuscular venous thrombosis, hip dislocations, Trendelenburg gait, and leg length discrepancies, showed no significant differences between the groups. Conclusion The OCM approach for bipolar hemiarthroplasty in patients aged 75 and above with femoral neck fractures offers significant early clinical benefits over the traditional PLA, including faster recovery, reduced postoperative pain, and enhanced early functional recovery.